Mental health of vulnerable groups experiencing a drought or bushfire: A systematic review. (13th April 2023) - Varshney, Karan; Makleff, Shelly; Krishna, Revathi N.; Romero, Lorena; Willems, Julie; Wickes, Rebecca; Fisher, Jane
Abstract: Natural hazards are increasing because of climate change, and they disproportionately affect vulnerable populations. Prior reviews of the mental health consequences of natural hazard events have not focused on the particular experiences of vulnerable groups. Based on the expected increase in fires and droughts in the coming years, the aim of this systematic review is to synthesize the global evidence about the mental health of vulnerable populations after experiencing natural hazards. We searched databases such as Ovid MEDLINE, EMBASE, CINAHL and Ovid PsycInfo using a systematic strategy, which yielded 3, 401 publications. We identified 18 eligible studies conducted in five different countries with 15, 959 participants. The most common vulnerabilities were living in a rural area, occupying a low socioeconomic position, being a member of an ethnic minority and having a medical condition. Common experiences reported by vulnerable individuals affected by drought included worry, hopelessness, isolation and suicidal thoughts and behaviors. Those affected by fire reported experiencing posttraumatic stress disorder (PTSD) and anger. These mental health problems exacerbated existing health and socioeconomic challenges. The evidence base about mental health in vulnerable communities affected by natural hazards can be improved by including standardized measures and comparison groups, examining the role of intersectional vulnerabilities, and disaggregating data routinely to allow for analyses of the particular experiences of vulnerable communities. Such efforts will help ensure that programs are informed by an understanding of the unique needs of these communities.